Clinical feasibility and acceptability of adding cognitive behavioral therapy to pharmacotherapy for drug‐resistant overactive bladder in women: A single‐arm pilot study. Issue 1 (3rd July 2020) - Funada, Satoshi; Watanabe, Norio; Goto, Takayuki; Negoro, Hiromitsu; Akamatsu, Shusuke; Uozumi, Ryuji; Kishimoto, Sanae; Ichioka, Kentaro; Segawa, Takehiko; Furukawa, Toshi A; Ogawa, Osamu
Abstract: Objectives: Drug‐resistant overactive bladder (OAB) represents an unmet medical need in that treatment options are limited. We developed a treatment model based on cognitive behavioral therapy and evaluated its feasibility and acceptability for drug‐resistant OAB in women. Methods: This was an open‐label, single‐arm, multicenter pilot study. We defined drug‐resistant OAB as OAB with moderate to severe symptoms despite pharmacotherapy for more than 12 weeks. A face‐to‐face intervention was prescribed as six sessions (30 minutes each) over 6 to 12 weeks according to a treatment manual. The effects were assessed by self‐reported questionnaires and frequency voiding charts (FVC) at baseline, during intervention, immediately after intervention, and at follow‐up. Results: Ten patients participated in this study. Median age was 72 years, median OAB Symptom Score was nine points, and median duration of prior treatment for OAB was 5.5 years at baseline. Two participants dropped out of the study. Among the remaining patients, the scores of the OAB Questionnaire subscales improved (effect size: 0.75‐1.73), and the mean urinary frequency in the FVC also improved from baseline (9.0 times, SD: 2.1) to follow‐up (6.2 times, SD: 1.2). All participants were satisfied with the intervention. There were no adverse events during this study. Conclusions: The new treatment based on cognitive behavioral therapy was well tolerated and feasible in women with drug‐resistant OAB. Further randomized research is needed to rigorously evaluate the efficacy of the treatment.